Nutritional status among the Shabar tribal children living in urban, rural and forest habitats of Orissa, India (Italian Journal of Public Health, 2010)
Background: The current trend towards increasing urbanization due to urban migration among the scheduledtribes in developing countries like India should be reflected in differential nutritional outcomes and itsassociated factors. The aims of the present study are to investigate the nutritional status amongst Shabarchildren living in urban, rural and forest habitats and factors associated to nutritional state.Methods: This cross sectional study was conducted among 577 Shabar children (boys and girls) aged 5 to 19years (258 urban, 195 rural and 124 forest). The anthropometric nutritional indices, socio-economic conditionand disease prevalence were used to evaluate the present conditions.Results: The results revealed that children from forest regions had the highest prevalence of under-nutritionfollowed by their rural and urban counterparts, 33.87%, 24.62% and 20.16%, respectively. Malaria prevalencein forest areas and economic conditions in rural and urban habitats might have been significantly related tounderweight and stunting.Conclusions: To reduce the prevalence and the extent of under-nutrition, it is essential to improve theeconomic conditions and to simultaneously carry out measurements for reducing malaria specifically in foresthabitats.
Keywords: under-nutrition; children; socio-economic factors; tribe; habitats; India